'We're all getting the bus Filipino young adults’ perception of their sexual self-concept through their reception on Netflix’s Sex Education. - Lampano, Alyka Mari Santos
The youth's media exposure to sexual content can positively and negatively develop their sexual self-concept, or assessment of their own sexual feelings and actions. While some have argued that such exposure has encouraged positive sexual attitudes among the youth, major studies linking media and sexuality reveal that it has largely produced harmful effects to their sexual self-concept by disseminating negative sexual scripts and inaccurate representations of sex and gender roles.